PENGARUH LITERASI AKUNTANSI DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI (SIA) TERHADAP AKURASI PENCATATAN KEUANGAN PADA UMKM DI PROVINSI BANTEN - Intan Purnama Sari; Abdul Hoer; Gilang Rissad Wongso Nugroho (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to analyze the effect of accounting literacy and the use of accounting information systems (AIS) on the accuracy of financial records in micro, small, and medium enterprises (MSMEs) in Banten Province, Indonesia. The research background is based on the importance of accurate financial records as a basis for decision-making, where the quality of such records is influenced by the competence of business actors and the support of recording technology. This research employed a quantitative approach with a causal design and multiple linear regression analysis. The sample consisted of 152 MSME owners or bookkeeping managers selected using simple random sampling. Data were collected through a structured questionnaire with a Likert scale, which was tested for reliability and validity prior to analysis. The results indicate that accounting literacy has a positive and significant effect on the accuracy of financial records (B = 0.225; t = 3.393; p = 0.001), as does the use of AIS (B = 0.019; t = 2.273; p = 0.002). Simultaneously, both variables explain 74% of the variation in financial record accuracy (R² = 0.74). These findings suggest that improving the accuracy of MSME financial records requires an integrated intervention consisting of practical accounting literacy training and the implementation of user-friendly, needs-based AIS. This study provides practical contributions for policymakers and MSME actors to design financial capacity-building programs that integrate human capabilities with technological support.Keywords : accounting literacy, accounting information systems, financial record accuracy, MSMEs.